Water from Mineral Springs – Composition and Application in Medicine and Cosmetics - Petrov, Petar (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2022)
The main objective of our study is to determine the composition of water from several mineral springs, test their antibacterial, antiviral and antifungal properties and compare them to find out the best ones to incorporate in medicinal and cosmetic products. To achieve this, samples from 8 mineral springs were subjected to elemental analysis for the determination of 70 elements using inductively coupled plasma-mass-spectrometry. Results showed that concentrations of the macro elements Mg, K, Ca and S were high in all of the samples even during the spring high water period. Elements with previously reported antibacterial, antiviral or antifungal properties (Au, Se, B, Mo, Ge, W, Sr) were also found in every sample in fairly high concentrations. The specific antimicrobial properties of the water of each mineral spring remain to be determined using agar well diffusion method and resazurin assay method. Furthermore, dry residue samples were analyzed with a Raman microscope and revealed several different crystalline structures, some of which are of a sulphate nature, which presumably contribute to the healing properties of the water.